2010
DOI: 10.1007/s10661-010-1814-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural factors and mining activity bearings on the water quality of the Choapa basin, North Central Chile: insights on the role of mafic volcanic rocks in the buffering of the acid drainage process

Abstract: This contribution analyzes water chemical data for the Choapa basin, North Central Chile, for the period 1980-2004. The parameters considered are As, Cu Fe, pH, EC, SO₄⁻², Cl⁻¹, and HCO[Formula: see text], from samples taken in nine monitoring stations throughout the basin. Results show rather moderate contents of As, Cu, and Fe, with the exception of the Cuncumén River and the Aucó creek, explained by the influence of the huge porphyry copper deposit of Los Pelambres and by the presence of mining operations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For water quality sampling, the record exhibits a rather variable time frequency, but in general, they were carried out monthly or bimonthly, previous to and following 2004, respectively. Details associated with chemical analyses conducted by the DGA are described in Oyarzun et al () and Parra et al (). For trend analysis (described below), records of parameters having concentrations less than the detection limit (i.e., censored values) were replaced by that limit.…”
Section: Data Sources and Analysismentioning
confidence: 99%
“…For water quality sampling, the record exhibits a rather variable time frequency, but in general, they were carried out monthly or bimonthly, previous to and following 2004, respectively. Details associated with chemical analyses conducted by the DGA are described in Oyarzun et al () and Parra et al (). For trend analysis (described below), records of parameters having concentrations less than the detection limit (i.e., censored values) were replaced by that limit.…”
Section: Data Sources and Analysismentioning
confidence: 99%
“…For example, the fate and speciation of iron, zinc, copper, lead, silver, arsenic, antimony, gold, and tin at the Rio Tinto and Rio Odiel in the Iberian Pyrite Belt (Spain) showed a strong dependency on seasonal changes (e.g., winter floods) and pH (ranging from 2.3 to 3.6), which controls the flux and partitioning of toxic metals into the Gulf of Cadiz (Braungardt, Achterberg, Elbaz‐Poulichet, & Morley, ). The connection between geological factors, mining operations, hydrology, and arsenic enrichment in sediments from the Elqui River watershed in northern Chile was described by several works (Galleguillos, Oyarzun, Maturana, & Oyarzun, ; Oyarzun et al, ; Oyarzun, Lillo, Higueras, Oyarzun, & Maturana, ; Oyarzun et al, ; Oyarzun, Oyarzun, Lillo, Maturana, & Higueras, ; Parra et al, ; Ribeiro et al, ). Galleguillos et al () reported that sedimentation at hydraulic facilities was used to attenuate the flux of arsenic in the upper Elqui watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Cu and Mn peaks obtained at Ll5 had maximum values of 59.5 and 22.5 mg/L, respectively. These values are higher at the Jequetepeque basin than those obtained from rivers located near mine sites worldwide, such as the Andean region, Asia, or Europe (Miller et al, 2004;Lin et al, 2007;Parra et al, 2011;Tarras Wahlberg and Nguyen, 2008;Sarmiento et al, 2011) and similar to values obtained at rivers affected by Rio Tinto Mine in Spain.…”
Section: Llapa Sub-basinsupporting
confidence: 75%